2015
DOI: 10.1136/annrheumdis-2015-eular.2274
|View full text |Cite
|
Sign up to set email alerts
|

OP0213 Systemic Sclerosis is Associated with a Unique Colonic Microbial Consortium

Abstract: BackgroundGastrointestinal tract (GIT) dysfunction affects most patients with systemic sclerosis (SSc) and is a leading cause of morbidity. While the etiology of SSc-related lower GIT dysfunction remains elusive, evidence suggests that bacterial overgrowth is a feature of SSc. However, no studies have directly examined the colonic microbial consortium of SSc patients.ObjectivesTo compare colonic microbial composition of SSc patients and healthy controls. To determine whether microbial composition alterations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…26,27 The first study to explore the GI microbiome in SSc (n = 17) demonstrated that patients with SSc had an altered microbiota composition compared with healthy age- and gender-matched controls in an analysis of colonic lavage specimens. 28 We subsequently compared the microbiota of two independent SSc cohorts (UCLA and OUH, n = 34) and found similar alterations in GI microbiota of SSc patients compared with controls in an analysis of stool specimens. 29 Similar findings were also reported by in an Italian SSc cohort including 59 SSc patients.…”
Section: New Approaches To Therapymentioning
confidence: 95%
See 1 more Smart Citation
“…26,27 The first study to explore the GI microbiome in SSc (n = 17) demonstrated that patients with SSc had an altered microbiota composition compared with healthy age- and gender-matched controls in an analysis of colonic lavage specimens. 28 We subsequently compared the microbiota of two independent SSc cohorts (UCLA and OUH, n = 34) and found similar alterations in GI microbiota of SSc patients compared with controls in an analysis of stool specimens. 29 Similar findings were also reported by in an Italian SSc cohort including 59 SSc patients.…”
Section: New Approaches To Therapymentioning
confidence: 95%
“…26,27 The first study to explore the GI microbiome in SSc (n = 17) demonstrated that patients with SSc had an altered microbiota composition compared with healthy age-and gender-matched controls in an analysis of colonic lavage specimens. 28 We subsequently compared the microbiota of two independent SSc cohorts (UCLA and OUH, n = 34) and found similar alterations in GI microbiota of SSc patients compared with controls in an analysis of stool specimens.29 Similar findings were also reported by in an Italian SSc cohort including 59 SSc patients.30 Cross-sectional data from a relatively large Swedish SSc cohort (n = 98) provided further evidence of an association between GI microbiome alterations and GI symptoms.31 This study also found that fecal calprotectin levels were higher in SSc patients with GI dysbiosis compared with SSc patients without dysbiosis, suggesting that inflamma-tion may moderate the relationship between GI microbiota alterations and GI symptoms in SSc.31 These studies have demonstrated that specific bacterial genera and species are associated with improvement or worsening in GI symp-toms, suggesting that a possible strategy for alleviating GI symptoms in SSc could target selective augmentation or elimination of specific bacterial species.…”
Section: Gi Microbiota Targetsmentioning
confidence: 99%
“…Moreover, recent host genome–microbiome association studies revealed that these genes were among those associated with microbiome composition. According to a study conducted by Volkmann et al ., which considered the gut microbiota of 17 systemic sclerosis patients and an equal number of healthy controls in order to reveal potential pathobionts, the differentiation of the gut microbiota associated with the disease shows significant similarities with the gut dysbiosis of Crohn’s disease [ 13 ]. This observation implies that autoimmune diseases may share characteristic host-microbiome variations.…”
Section: Microbiome As Quantitative Traitmentioning
confidence: 99%
“…In addition, studies directed to the nature and potential role of the gut microbiome present a new and exciting avenue of research that one day may lead to a better understanding of SSc pathogenesis. 2,17…”
mentioning
confidence: 99%